ASSESSMENT OF FOOD AND NUTRIENT INTAKE OF COMMUNITIES ACROSS THREE AGRO-BIODIVERSITY HOTSPOTS IN INDIA - Raghu, Prabhakaran T.; Kalaiselvan, N.N; Nambi, Arivudai V.; Guptha B, Chandra; Mahana, R.K; Venkatesan, G.; Arunraj, R.; Philip P.I, Maria (European Scientific Journal, ESJ, 2014)
Balanced and adequate nutrition is important in improving the health of the community in general and of vulnerable groups in particular. Assessment of the nutritional status of a community is important for development of implementation strategies and suitable policies. Dietary assessment indicates whether intake of macro and micro nutrient are adequate. Anthropometric measurements and comparisons of nutrient intakes with reference values are easy and non-invasive, economical and sufficiently reliable methods for the determination of nutritional status. The present study uses micro-level data drawn from 24 hours recall diet survey to calculate the mean food and nutrient intake by communities in three agro-biodiversity hotspots. The 24 hours recall diet survey was carried out among households in three study locations during June to November 2013 among the project intervention and non-intervention groups. Information on age, sex, physiological status, physical activity of the household members who took meals during the previous 24 hours was collected for computing consumption unit. The result shows that cereals are the chief source of energy in the study locations contributing 70-80% of the daily energy intake. Mean intake of green leafy vegetable are negligible in the study locations. The intake of sugar and jaggery among the intervention group of Meenangadi is 48% higher than recommended dietary intake, while in the non-intervention group it is 28% higher; and 20% higher among the nonintervention group in the Kolli Hills. The intake of vitamin A is the lowest among other nutrients across the internvention and non-intervention groups in the study locations.